2017
DOI: 10.1002/mpr.1593
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the hierarchical general factor model of psychopathology in young adults

Abstract: There is evidence that models of psychopathology specifying a general factor and specific second-order factors fit better than competing structural models. Nonetheless, additional tests are needed to examine the generality and boundaries of the general factor model. In a selected second wave of a cohort study, first-order dimensions of psychopathology symptoms in 499 23- to 31-year-old twins were analyzed. Using confirmatory factor analysis, a bifactor model specifying a general factor and specific internalizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 28 publications
5
45
0
2
Order By: Relevance
“…High loadings of personality disorders on the P factor and high loadings of alcohol use disorders on the externalizing factor were consistent with results from other studies in general and prison populations [16, 22]. Recent studies indicated that borderline personality disorders were comorbid with several other forms of psychopathology and associated with more than one underlying dimension (i.e., the distress subfactor of the internalizing dimension and the externalizing dimension) [43, 44].…”
Section: Discussionsupporting
confidence: 76%
“…High loadings of personality disorders on the P factor and high loadings of alcohol use disorders on the externalizing factor were consistent with results from other studies in general and prison populations [16, 22]. Recent studies indicated that borderline personality disorders were comorbid with several other forms of psychopathology and associated with more than one underlying dimension (i.e., the distress subfactor of the internalizing dimension and the externalizing dimension) [43, 44].…”
Section: Discussionsupporting
confidence: 76%
“…Although there is evidence that UD attachment increases vulnerability to psychopathology in general, it is unknown how unresolved trauma relates to the abnormalities in brain structure and function that are commonly found in patients with psychopathology (Caspi et al., ; Lahey et al., ). In the current study, we therefore examined whether UD attachment is related to brain abnormalities across multiple psychiatric diagnoses.…”
mentioning
confidence: 99%
“…Model bifaktor sebenarnya bukan gagasan baru, namun popularitasnya di kalangan peneliti sosial mulai meningkat dalam beberapa tahun terakhir. Model bifaktor sudah diterapkan pada pengukuran di bidang kesehatan mental (Brouwer & Meijer, 2013;Lahey et al, 2018), kepribadian (Biderman et al, 2018), dan pendidikan (Scherer & Gustafsson, 2015;Wang, Kim, Dedrick, Ferron, & Tan, 2018). Sebagai pengantar, Modul 1 membahas model bifaktor secara konseptual.…”
Section: Pengantarunclassified